The Influence of Organizational Culture and Leadership Style on The Effectiveness of The Main Duties and Functions of The Indonesian National Naval Historical Service - Rendy Meidiyanto; Enjang Sudarman; Sukiman Sukiman (Dinasti International Journal of Management Science, 2026)
This research has the following objectives: analyzing the influence of organizational culture on the effectiveness of the implementation of main tasks and functions, analyzing the influence of leadership style on the effectiveness of the implementation of main tasks and functions, testing the simultaneous influence of organizational culture and leadership style on the effectiveness of the implementation of main tasks and functions, the organizational culture variable (X1) is 8.501, while the ttable value for n = 49 is 2.013 . So 8.501 > 2.013, there is an influence of leadership style on the effectiveness of the implementation of main tasks and functions, leadership style (X2) is 7.002, while the ttable value for n = 49 is 2.013. So 7.002 > 2.013, there is an influence of organizational culture and leadership style together towards the effectiveness of the implementation of the main tasks and functions. This is proven by the results obtained ANOVA test or f count obtained a calculated F value of 41.339 While the Ftable (a0.05) for n = 46 is 2.81. So the calculated F > from the Ftable (a0.05) or 41.339 > 2.81 with a significance level of 0.000 because 0.000 < 0.05.